Upaya Pengembangan Objek Wisata Air Terjun Tiga Pangung di Desa Ulak Bandung Kec. Muara Sahung Kab. Kaur - Dewi Susila Wati; Juim Juim; Titi Darmi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
The purpose of this study is to find out the efforts and factors inhibiting the development of Tiga Pangung Waterfall Tourism Object in Ulak Village Bandung Kec. Muara Sahung Kab. Kaur. Researchers used qualitative descriptive research methods. The data source consists of primary and secondary data. Primary data is obtained through interviews to management actors. Data analysis techniques used by researchers through the stages of data collection, data reduction, data presentation, and verivication or data validation. Data validation is done by confirmation to the public. The results of research efforts to develop The Three Pangung Waterfall Tourism Object in Ulak Village Bandung Kec. Muara Sahung Kab. Kaur done quite well this is seen from the role of village officials, village heads, communities and the role of coral cadets in developing objerk Wisata empowerment of roads, maintaining cleanliness and infrastructure advice provided at the Three Pangung Waterfall Tourism Object in Ulak Village Bandung Kec. Muara Sahung Kab. Kaur. Factors Inhibiting the Development of Three Pangung Waterfall Attractions in Ulak Village Bandung Kec. Muara Sahung Kab. Kaur, which was found to include a lack of facilities and infrastructure, human resources that do not play an active role, funds and lack of coaching conducted by the tourism and cultural office.